Miss Kopp's midnight confessions [compact disc, unabridged] - Stewart, Amy (Stewart, Amy. Kopp sisters novel., 2017)
Deputy sheriff Constance Kopp is outraged to see young women brought into the Hackensack jail over dubious charges of waywardness, incorrigibility, and moral depravity. The strong-willed, patriotic Edna Heustis, who left home to work in a munitions factory, certainly doesn't belong behind bars. And sixteen-year-old runaway Minnie Davis, with few prospects and fewer friends, shouldn't be publicly shamed and packed off to a state-run reformatory. But such were the laws--and morals--of 1916. Constance uses her authority as deputy sheriff, and occasionally exceeds it, to investigate and defend these women when no one else will. But it's her sister Fleurette who puts Constance's beliefs to the test and forces her to reckon with her own ideas of how a young woman should and shouldn't behave.